Ferrets as a model for tuberculosis transmission - Gupta, Tuhina; Somanna, Naveen; Rowe, Thomas; LaGatta, Monica; Helms, Shelly; Owino, Simon Odera; Jelesijevic, Tomislav; Harvey, Stephen; Jacobs, Wayne; Voss, Thomas; Sakamoto, Kaori; Day, Cheryl; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Until the COVID-19 pandemic came upon us, tuberculosis was the leading cause of human death due to a single infectious agent. Until successfully treated, infected individuals may continue to transmit Mycobacterium tuberculosis bacilli to contacts. As with other respiratory pathogens such as SARS-CoV-2, modeling the process of person-to-person transmission will inform efforts to develop vaccines and therapies that specifically impede disease transmission. The ferret (Mustela furo), a relatively inexpensive, small animal has been successfully employed to model transmissibility, pathogenicity, and tropism of influenza and other respiratory disease agents. Ferrets can become naturally infected with Mycobacterium bovis and are closely related to badgers, well known in Great Britain and elsewhere as a natural transmission vehicle for bovine tuberculosis. Herein, we report results of a pilot study demonstrating that within 7 weeks of intratracheal infection with a high dose (>5 x 103 CFU) of M. tuberculosis bacilli, ferrets develop symptoms and pathological features similar to acute disease reported in larger animals. Natural transmission of this pathogen was also examined. Acutely-infected ferrets transmitted M. tuberculosis bacilli to co-housed naïve sentinels; the sentinels developed variable disease symptomologies similar to those reported for humans exposed to an active tuberculosis patient in a closed setting. Aerosol-only transmission was examined between ferrets separated by a wire mesh. Transmission efficiency was lower, possibly due to the intense airflow within the caging system. A comprehensive overview of the parameters used for initiating and monitoring M. tuberculosis disease and transmission in ferrets, and analysis of the results in the context of other respiratory disease transmission studies is presented. The findings support further assessment of this model system for tuberculosis transmission including the testing of prevention measures and vaccine efficacy.